The low chances of nonprofit radio faced with the Audiovisual General Law. The incomprehensible exclusion of public university radio stations - Durán Mañes, Ángeles (Derecom. Derecho de la Comunicación y de Nuevas Tecnologías, 2024)
In Spain, the cultural radio, since its origin, has been left into a strange lawless status. Different regulations have recognized the cultural radio, but its development has been restricted as no licenses have been granted. The Audiovisual General Law raised somehope around its regularization and also around the development of the Third Sector within  broadcasting communication. However, it leads these nonprofit radio stations to an uncertain survival. Furthermore, it only recognizes the private entities as possible holders, thus leaving out a score of public university radios, forcing them to compete for commercial licenses or to disappear.
Keywords: Cultural Radio; Comunity Radio; University Radio; Audiovisual General Law; Third Sector Communication